Intimacy versus isolation: A qualitative study of sexual practices among sexually active HIV-infected patients in HIV care in Brazil, Thailand, and Zambia - Elizabeth F. Closson (2018)
© 2015 Closson et al. The success of global treat ment as prevention (TasP) efforts for individuals living with HIV/AIDS (PLWHA) is dependent on successful implementation, and therefore the appropriate contribution of social and behavioral science to these efforts. Understanding the psychosocial context of condomless sex among PLWHA could shed light on effective points of intervention. HPTN 063 was an observational mixed-methods study of sexually active, in-care PLWHA in Thailand, Zambia, and Brazil as a foundation for integrating secondary HIV prevention into HIV treatment. From 2010-2012, 80 qualitative interviews were conducted with PLWHA receiving HIV care and reported recent sexual risk. Thirty men who have sex with women (MSW) and 30 women who have sex with men (WSM) participated in equal numbers across the sites. Thailand and Brazil also enrolled 20 biologically-born men who have sex with men (MSM). Part of the interview focused on the impact of HIV on sexual practices and relationships. Interviews were recorded, transcribed, translated into English and examined using qualitative descriptive analysis. The mean age was 25 (SD = 3.2). There were numerous similarities in experiences and attitudes between MSM, MSW and WSM across the three settings. Participants had a high degree of HIV transmission risk awareness and practiced some protective sexual behaviors such as reduced sexual activity, increased use of condoms, and external ejaculation. Themes related to risk behavior can be categorized according to struggles for intimacy and fears of isolation, including: fear of infecting a sex partner, guilt about sex, sexual communication difficulty, HIV-stigma, and worry about sexual partnerships. Emphasizing sexual health, intimacy and protective practices as components of nonjudgmental sex-positive secondary HIV prevention interventions is recommended. For in-care PLWHA, this approach has the potential to support TasP. The overlap of themes across groups and countries indicates that similar intervention content may be effective for a range of settings.